2017
DOI: 10.15324/kjcls.2017.49.3.308
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Perceived Stress Scale and Carotid Intima-Media Thickness Using Ultrasonography in University Students

Abstract: 고려대학교 안산병원 신경과, 3 강원대학교 의학과대학원 진단검사의학전공Carotid artery intima-media thickness (CIMT) test is a standardized ultrasound procedure that screens for and monitors atherosclerosis in a safe and non-invasive manner, even in individuals with no symptoms of heart disease. The purpose of this study was to research the relationship between CIMT, as measured by ultrasonography, and the degree of individual perceived stress. There was a total of 168 (male: 46, female: 122) university students in Suwon-si, Gyeonggi-do, Kor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
(18 reference statements)
0
17
0
Order By: Relevance
“… 12 Thresholds used in the literature consider the stress level low for scores between 0 and 13; moderate, between 14 and 26; and high, greater than 26. 13 , 14 We measured depression using the 13-item Beck Depression Inventory (BDI-13). Each question is rated from 0 to 3 to obtain a score ranging from 0 to 39.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 Thresholds used in the literature consider the stress level low for scores between 0 and 13; moderate, between 14 and 26; and high, greater than 26. 13 , 14 We measured depression using the 13-item Beck Depression Inventory (BDI-13). Each question is rated from 0 to 3 to obtain a score ranging from 0 to 39.…”
Section: Methodsmentioning
confidence: 99%
“… 18 Outcomes were the presence of severe self-reported symptoms, ie, the presence of suicidal thoughts or a high score on at least 1 scale (ie, IES-R >36; PSS-10 >26; BDI-13 >15; or STAI-Y2 >55). 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the early prevention of CV and cerebrovascular diseases has become a focus of current research. Preclinical atherosclerosis has been related to higher coronary heart disease and stroke rates [9]. Cardiovascular disease (CVD) is the leading cause of death and a major cause of disability worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Their data are in accordance with our results. Kim et al [18] found no correlation between perceived stress and the cIMT. And even though we found a relationship between them, after adjusting for other variables, it disappeared.…”
Section: Discussionmentioning
confidence: 99%